Relating Invasibility and Invasiveness: Case Study of Impatiens parviflora - Krokaitė, Edvina; Janulionienė, Rasa; Jocienė, Lina; Rekašius, Tomas; Rajackaitė, Giedrė; Paulauskas, Algimantas; Marozas, Vitas; Kupčinskienė, Eugenija (Frontiers in Ecology and Evolution, 2022)
Data on alien species show that plant invasions are caused by a complex combination of characteristics of invasive species (invasiveness) and characteristics of invaded environment (invasibility). Impatiens parviflora is one of Europe’s top invasive species. The present study aimed to evaluate molecular diversity of populations of highly invasive in Lithuania I. parviflora by applying several DNA markers and relating genetic parameters to abiotic and biotic environment. For sampling, urban forests, riparian forests, and agrarian shrublands were selected. Three different DNA-based techniques, Simple Sequence Repeats (SSR), Inter Simple Sequence Repeat (ISSR) markers, and Random Amplified Polymorphic DNA (RAPD), were used for detecting genetic variation between 21 populations. All population individuals were monomorphic and homozygotic for four loci and heterozygotic for one locus by SSR analysis. Hierarchical analyses of molecular variance at ISSR and RAPD loci revealed significant differentiation of populations depending on geographic zones of the country. Bayesian Structure analyses of molecular data demonstrated existence of many genetic clusters and this finding is in support to multiple introduction of the species. The polymorphism extent at ISSR loci was positively correlated with the total coverage of herbaceous plant species. The coverage by I. parviflora was negatively correlated with the total number of herbaceous species and light in the sites. Our results indicate that Lithuanian sites with I. parviflora might be distinguished by high soil nutrient levels. According to the principal component analysis, the coverage by I. parviflora was a more important variable of populations compared to molecular data or parameters of abiotic environment. In conclusion, complexity of invasibility and invasiveness factors determine the variability of I. parviflora sites, including genetic traits, coverage of invasive species and conditions of environment that were significant and interrelated.